KINERJA DINAS KEBERSIHAN DAN PERTAMANAN KOTA PONTIANAK DALAM PENGELOLAAN SAMPAH DI KELURAHAN SAIGONKECAMATAN PONTIANAK TIMUR - Queen Mona Oktaviani E.01108117 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This article is motivated to investigate the performance of the sanitation department and landscaping Pontianak city in saigon waste management in urban districts in the eastern pontianak handle the amount of garbage strewn and lack of trash that does not fit into the population.To be more clear, we propose the following research issues: “How Performance Management and Control Field At Cleanliness and Sanitation Department of Pontianak in Pontianak District East Village Saigon is assessed through aspects of collection, transportation and processing of waste?”. As for the purpose of this research is you want to know and analyze the performance of Field How Cleanliness Management and Control of the Department of Hygiene and Pontianak in waste management in Saigon Village District East Pontianak in aspects of the collection, transport, and waste management. Research methods here the authors use descriptive research and data collection techniques used in this study is the observation, interviews, documentation, while data analysis techniques the author uses descriptive qualitative technique in which the collected data is processed and analyzed qualitatively.From the analysis of the data showed that based on research and discussions that have been described, it can be concluded that the quality of the performance of Field Management and Control of the Cleanliness and Sanitation Department of Pontianak is not maximized. Location of temporary shelters still a ride on the side of the highway and not official. The procedure is not optimal due to lack of transport fleet quantity used so inefficiently working time. Department of Hygiene and Pontianak should have more than one location and spread of temporary shelters to avoid the buildup of trash. On the transport procedure, should the fleet used to transport garbage from trash temporary shelter to the shelter late to be fixed and added to the quality of staff performance can be more efficient.Keywords: Performance, Management, Aspect, Quality, Quantity.